Diccionario Gramsciano (1926-1937) (Tertulias, 2022)
For the Spanish version of this dictionary, 101 slogans were selected from among the voices that constitute the backbone of Gramsci's thought during his prison period (1926-1937). The writing of the entries was originally done by privileging textual quotations, in order to suggest an attention to the text that is not always found in criticism, and the chronological sequence that allows us to recognize the strategy of Gramsci's thinking and writing in his notebooks was maintained. The writing of the voices thus appears, to the reader's eyes, as clean as possible, spun only by a discreet intervention of the authors and without interfering with references to the debates between the various interpretations existing in the literature on the topics, aspects and concepts presented.